2018
DOI: 10.1051/epjconf/201817702003
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Shielding- Collimator Parameters for ING-27 Neutron Generator Using MCNP5

Abstract: Abstract. Neutron generators are now used in various fields. They produce only fast neutrons; D-D neutron generator produces 2.45 MeV neutrons and D-T produces 14.1 MeV neutrons. In order to optimize shielding-collimator parameters to achieve higher neutron flux at the investigated sample (The signal) with lower neutron and gamma rays flux at the area of the detectors, design iterations are widely used. This work was applied to ROMASHA setup, TANGRA project, FLNP, Joint Institute for Nuclear Research. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This is because reinforcement learning methods, especially the off-policy ones, rely on previous experiences during training. These advantages do allow for more stability in deploying DRL models in critical applications, such as nuclear engineering [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…This is because reinforcement learning methods, especially the off-policy ones, rely on previous experiences during training. These advantages do allow for more stability in deploying DRL models in critical applications, such as nuclear engineering [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The simulated setup is replicating the Romasha experimental setup located in Frank Laboratory at the Joint Institute for Nuclear Research (JINR) as demonstrated in Fig. 3 31 . The Romasha setup consisted of an ING-27 D-T neutron generator that generates 14.1 meV neutrons, six iron sheets collimator, and Ten BGO detectors located in a semicircle of 30 cm radius, as demonstrated in Fig.…”
Section: Data Generationmentioning
confidence: 99%
“…3. Dimensions of the setup are listed in Supplementary Table 2 22,31 . The gamma rays emitted due to neutron interactions with the sample travel in different directions.…”
Section: Data Generationmentioning
confidence: 99%
“…Other researchers focused on the implementation of deep neural networks in different applications such as developing deep neural networks (DNNs) capable of helping in optimizing the radiotherapy treatment plan in the Oncology field of study [14]. Others worked on developing interconnected regressors and a classifier to differentiate between shielded explosive and non-explosive hydrocarbons using the signals obtained from the prompt gamma neutron activation analysis technique (PGNAA) based on the ROMASHA setup located in JINR, Russia [15,16]. Also, Hosny et al worked on developing a pipeline of interconnected K-nearest neighbor (KNN) regressors and a decision tree classifier capable of discriminating explosives from non-explosive hydrocarbons when the investigated sample was not shielded [17].…”
Section: Introductionmentioning
confidence: 99%